Austrian tricentric real-life analysis of molecular profiles of metastatic biliary tract cancer patients - Taghizadeh, Hossein; Schmalfuss, Theresa; Maj-Hes, Agnieszka; Singer, Josef; Prager, Gerald W. (Frontiers in Oncology, 2023)
Introduction: Metastatic biliary tract cancer (BTC) is a rare and aggressive entity associated with poor prognosis. It represents a major challenge for adequate treatment strategies. In recent years, BTC has become a model for precision medicine in gastrointestinal oncology. Therefore, the analysis of the individual molecular profile in BTC patients may lead to targeted therapies for the benefit of patients. Methods: In this Austrian, tricentric, real-world, retrospective analysis, we investigated patients diagnosed with metastatic BTC who underwent molecular profiling between 2013 and 2022. Results: In total, 92 patients were identified in this tricentric analysis and 205 molecular aberrations, including 198 mutations affecting 89 different genes in 61 patients were found. The predominant mutations were in KRAS (n=17; 22.4%), TP53 (n=17; 22.4%), PIK3CA (n=7; 9.2%), FGFR2 (n=7; 9.2%), DNMT3A (n=7; 9.2%), IDH1 (n=7; 9.2%), IDH2 (n=6; 7.9%), CDKN2A (n=6; 7.9%), BAP1 (n=4; 5.3%), NF1 (n=4; 5.3%), and NF2 (n=4; 5.3%). Three patients had HER2 amplification. MSI-H status and FGFR2 fusion genes were each observed in two different patients. One patient had a BRAF V600E mutation. Eventually, 10 patients received targeted therapy, of whom one-half derived clinical benefit. Conclusions: Molecular profiling of BTC patients is implementable in routine clinical practice and should be regularly employed to detect and exploit molecular vulnerabilities.